Potencjał literaturoznawczy i kulturoznawczy tekstów patrystycznych i teologicznych. Wybrane przykłady - Gaj, Beata (Vox Patrum, 2024)
The article discusses the issue of literary and cultural reflection on patrological and theological texts. The outline of possible analysis of texts related to the history of doctrine and the dissemination of Christianity using methods other than those developed in patristics and theology shows ways to enrich both the spectrum of interpretation of texts originating from Christian antiquity or its reception, as well as the possibilities of disseminating knowledge about them. For exemplification, texts by three authors of Christian antiquity were selected: Damasus I, Firmicus Maternus, Filaster of Brescia, and native reception texts from Poland (Walenty of Warta, Andreas Stredonius), referring both to the achievements of ancient literature, Christian apologetics, and to the literary tendencies of the era (16th and 17th centuries).